Kemampuan Menulis Puisi Pada Siswa Kelas X Man 2 Kepahiang - Helsi Pramesti; Nafri Yanti; Padi Utomo (Jurnal Korpus, 2026)
The purpose of this study was to determine the Poetry Writing Ability of Class X Students of MAN 2 Kepahiang. This study used a descriptive method with a quantitative approach. The population in this study were all class X students of MAN 2 Kepahiang totaling 182 students. While the sample in this study used the Purposive sampling technique, namely sampling carried out according to the requirements of 14% of the population, namely 26 students. The data collection technique used the documentation technique, namely the results of students' poetry writing tests. The ability to write poetry is assessed from five aspects, namely the diction aspect, the language style aspect, the typography aspect, the theme aspect, and the message aspect. The data analysis technique used in this study was simple statistics by calculating the average value. The results of this study indicate that the average value of the ability to write poetry in class X students of MAN 2 Kepahiang is 72 with a good category. The average value of students' poetry writing ability in the aspect of diction or word choice is 20 with a good category, the average of students' poetry writing ability in the aspect of language style (figure of speech) is 18 with a good category, the average of students' poetry writing ability in the aspect of theme is 17 with a very good category, and the average of students' poetry writing ability in the aspect of message is 17 with a very good category. The conclusion of this study is that students of class X MAN 2 Kepahiang are able to write poetry well, although there are still some students who are still categorized as sufficient in writing poetry, but overall students have been able to write poetry by paying attention to the elements of construction well.